Electrochemically modified Corey–Fuchs reaction for the synthesis of arylalkynes. The case of 2-(2,2-dibromovinyl)naphthalene - Fabiana Pandolfi; Isabella Chiarotto; Marta Feroci (Beilstein Journal of Organic Chemistry, 2018)
The electrochemical reduction of 2-(2,2-dibromovinyl)naphthalene in a DMF solution (Pt cathode) yields selectively 2-ethynylnaphthalene or 2-(bromoethynyl)naphthalene in high yields, depending on the electrolysis conditions. In particular, by simply changing the working potential and the supporting electrolyte, the reaction can be directed towards the synthesis of the terminal alkyne (Et4NBF4) or the bromoalkyne (NaClO4). This study allowed to establish that 2-(bromoethynyl)naphthalene can be converted into 2-ethynylnaphthalene by cathodic reduction.